Emoji and communicative action: The semiotics, sequence and gestural actions of 'face covering hand'. (December 2018) - Gibson, Will; Huang, Pingping; Yu, Qianyun
Highlights: Conversation analysis facilitates an examination of the communicative function of emoji. Emoji perform communicative work related to the textual context. Gestures indexed by emoji are important referents in their analysis. Research should focus on the process of emoji selection and technology interfaces. Abstract: This paper uses conversation analysis to explore the communicative functions of one emoji in a mobile reading community in China. In contrast to semiotic approaches to emoji that focus on their cultural signification, or that treat them as reflections of users' inner intensions, we analyse emoji as communication phenomena by exploring their relation to other textual actions in the production of text-talk. The emoji analysed here functioned as a laughter token, and performed specific interactional work related to laughter. We conclude that conversation analysis offers an important corrective to abstracted semiotic analysis and a useful resource for exploring the demonstrable meaning of emoji for interlocutors. However, we also emphasise the importance of capturing the process of composing messages, the challenges of dealing with the variety of forms that emoji take and their relation to gestural and other actions in face to face communication.